A Philosophical Reflection in Controlling the Property and Self-ownership - Qusthan Firdaus (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2019)
This study aims to describe the philosophical reflection in controlling property and self-ownership. A crucial point about the concept is whether or not the non-separation between the owner and what is owned is plausible. There are differences between the way we exercise our rights to property in things and to property in persons. For instance, if we have rights to do anything with our property in things, therefore we also have rights to do anything with our property in persons, provided that there is no violation on others' rights. The results shows that in contrast, we can morally destroy our property in things if we could achieve our ends by doing it. In short, although we have rights either to destroy property in things and property in persons, we are not prone to exercise such rights on our property in persons.